Socio-economic profile of açaí production managed in rural communities in the Municipality of Igarapé-Miri, Pará State (Research, Society and Development, 2021)
The assai tree (Euterpe oleracea Mart.) is a palm that occurs naturally in the floodplain environment of the Amazon estuary, which is extremely important in terms of food and income generation for riverside dwellers. The research analyzed the socio-economics of assai production in the communities of Anapú, Caji and Meruú, municipality of Igarapé-Miri (Para State) through interviews with the application of 61 semi-structured questionnaires together with açai producers, in addition to field explorations with photographic records and geographic coordinates, opting for an intentional sampling. The families collect 36,139.38 kg of fruit during the year, 61.53% in the harvest and 38.47% in the off-season, with a productivity of 3,013.90 kg/ha. It was found that most producers are male with an average of 50 years old, low level of education, native and with income ranging from 1 to 2 minimum wages per month. Residences have rustic infrastructure and lack of adequate sanitary sewage. However, the small portion of masonry houses and tiled floors indicates the desire for improvement.